Fixed Costs of Adjustment, Coordination, and Industry Investment - Doyle, Joanne M.; Whited, Toni M. (The Review of Economics and Statistics, 2001)
We test whether smooth industry-level investment dynamics result from explicit aggregation of asynchronous and possibly lumpy firm-level investment. We compare the deviations of optimal from actual firm behavior across industries categorized by their ratios of idiosyncratic uncertainty to the sum of idiosyncratic and aggregate uncertainty. The deviations are represented by the residuals of a cointegrating regression that is derived from the firm's first-order condition under no adjustment costs. In support of models with asynchronous firm decisions, we find a significant negative relationship across industries between idiosyncratic uncertainty and the persistence of these residuals.